Analysis of Acceptance and Use of Internet Service for The Preparation of Financial Reports Using the Unified Theory of Acceptance and Use Technology (UTAUT) - I Wayan Megayana; I Gusti Ngurah Agung Suaryana (PT Mattawang Mediatama Solution, 2023)
This paper was conducted to analyze Acceptance and Use of Internet Services for The Preparation of Financial Reports using UTAUT. Data collected using questionnaires then tested using Partial Least Square (PLS). The research sample is 147 respondents. Examination results showing performances expectancies, Social influences, Effort expectancies give positive significant impacts towards behaviorals intention. Furthermore, Performance expectancies, Effort expectancies, Behavioral intention positively and significantly affect use behavior. Actual experience can strengthen the effect of performance expectancies on behavioral intention but cannot strengthen social influences towards behavioral intention. Finally, actual experience can not strengthen the influence of effort expectancies towards behavioral intention.